If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 130 + -25t = 15 Solving 130 + -25t = 15 Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '-130' to each side of the equation. 130 + -130 + -25t = 15 + -130 Combine like terms: 130 + -130 = 0 0 + -25t = 15 + -130 -25t = 15 + -130 Combine like terms: 15 + -130 = -115 -25t = -115 Divide each side by '-25'. t = 4.6 Simplifying t = 4.6
| (4x-3)2+7=39 | | x*3+x*2-12=0 | | 5x^2+20x-30=15 | | 23x+6-27x=2-8 | | 5c+2=5c+4 | | z=10-2x^2 | | f(-5)=(x^2)-5x+7 | | Ax+3=6x+b | | 3x^2+2x+10=900 | | 4x-8=12(4+3x) | | -19(5c-8)-12c= | | (4x-12)(x+7)=0 | | p=140-0.5x | | -6=2x-1x | | 6x^2+22x-18=0 | | y=-a-x | | Ln(x)=24 | | 6x^2+22-18=0 | | 6a=6a+12 | | x(x-4)(x+14)=0 | | ax+1=bx-y | | P=80x-.4x^2-200 | | .8x-4=2x-3 | | 21x-5x=32 | | 9x+1=6x+6 | | 32-6x=14-9x | | z-i=2z-1 | | x+7-6x=-23 | | 4x+14=23 | | 2y^2+9y-2=(y+2)(y-7) | | -4x+5+2x=-19 | | 11(k-1)=7(k-9.015228426) |